Comparative Study of the Effect of Different Drying Methods on Physicochemical Properties of Tomatoes - Olaniyi Hammed, Salaudeen; Paul Abuh , Omale; Izuchukwu Augustus, d Daraojimba (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
This study was conducted in the Department of Agricultural and Environmental Engineering Laboratory to compare the effect of drying methods on physico-chemical properties of tomato (Solanumly copersicum). Two drying methods at two different temperatures 50 0C and 100 0C on two varieties of tomatoes were carried out. The two varieties were processed into powdered form and some of the physico-chemical properties (moisture content, pH, protein, crude ash, soluble solids, and ascorbic acid) were tested. At 50 0C, moisture content ranged from 7.85 – 8.08, protein ranged from 11.04 – 12.12, pH ranged from 5.58 – 5.92, crude ash ranged from 8.70 -12.02, soluble solids ranged from 1.42 – 1.78 and ascorbic acid ranged from 6.55 – 7.49 while at 100 0C moisture content ranged from 6.90 – 7.41, protein ranged from 10.12 – 10.79, pH ranged from 5.27 – 5.36, crude ash ranged from 9.50 - 9.93, soluble solids ranged from 1.84 – 2.10 and ascorbic acid ranged from 8.59 – 9.23. The analysis of variance was done on this experimental result and it was discovered that variety, drying methods and drying temperature all had significant effects on the investigated physico-chemical properties of tomato powder at (p<0.05. From the result generated from the different varieties and the different drying methods used it suggests that the oven drying method is better amongst the two drying methods because it retained more percentages of the physico-chemical properties than the microwave method but they are both safe for human consumption.